The role of mitochondrial labile iron in Friedreich's ataxia skin fibroblasts sensitivity to ultraviolet A - Reelfs, Olivier (Royal Society of Chemistry, 2019)

(untitled) (Metallomics)
Mitochondrial labile iron (LI) is a major contributor to the susceptibility of skin fibroblasts to ultraviolet A (UVA)-induced oxidative damage leading to necrotic cell death via ATP depletion. Mitochondria iron overload is a key feature of the neurodegenerative disease Friedreich's ataxia (FRDA). Here we show that cultured primary skin fibroblasts from FRDA patients are 4 to 10-fold more sensitive to UVA-induced death than their healthy counterparts. We demonstrate that FRDA cells display higher levels of mitochondrial LI (up to 6-fold on average compared to healthy counterparts) and show higher increase in mitochondrial reactive oxygen species (ROS) generation after UVA irradiation (up to 2-fold on average), consistent with their differential sensitivity to UVA. Pre-treatment of the FRDA cells with a bespoke mitochondrial iron chelator fully abrogates the UVA-mediated cell death and reduces UVA-induced damage to mitochondrial membrane and the resulting ATP depletion by a factor of 2. Our results reveal a link between FRDA as a disease of mitochondrial iron overload and sensitivity to UVA of skin fibroblasts. Our findings suggest that the high levels of mitochondrial LI in FRDA cells which contribute to high levels of mitochondrial ROS production after UVA irradiation are likely to play a crucial role in the marked sensitivity of these cells to UVA-induced oxidative damage. This study may have implications not only for FRDA but also for other diseases of mitochondrial iron overload, with the view to develop topical mitochondria-targeted iron chelators as skin photoprotective agents.